(untitled) (PerCursos, 2017)
All over the world, natural hazards associated to climate change effects are increasing in frequency and threatening urban development dynamics while increasing human losses and economic expenditure. The objective of this paper is to investigate how post-disaster recovery and reconstruction should be addressed when associated with a scenario of urban poverty, lack of governance and social inequalities that can affect or restrict the capacity of a low-income country like Haiti to respond to natural hazards. Keywords: Disaster. Post-disaster. Recovery. Reconstruction. Haiti.